Introduction of a weighting scheme for the X‐ray restrained wavefunction approach: advantages and drawbacks. Issue 1 (21st November 2022) - Macetti, Giovanni; Genoni, Alessandro
Abstract : A weighting scheme for the X‐ray restrained/constrained wavefunction approach is proposed. Test calculations were carried out with both theoretical and experimental X‐ray diffraction data to assess advantages and drawbacks of the proposed approach in the different cases. Abstract : In a quite recent study [Genoni et al. (2017). IUCrJ, 4, 136–146], it was observed that the X‐ray restrained wavefunction (XRW) approach allows a more efficient and larger capture of electron correlation effects on the electron density if high‐angle reflections are not considered in the calculations. This is due to the occurrence of two concomitant effects when one uses theoretical X‐ray diffraction data corresponding to a single‐molecule electron density in a large unit cell: (i) the high‐angle reflections are generally much more numerous than the low‐ and medium‐angle ones, and (ii) they are already very well described at unrestrained level. Nevertheless, since high‐angle data also contain important information that should not be disregarded, it is not advisable to neglect them completely. For this reason, based on the results of the previous investigation, this work introduces a weighting scheme for XRW calculations to up‐weight the contribution of low‐ and medium‐angle reflections, and, at the same time, to reasonably down‐weight the importance of the high‐angle data. The proposed strategy was tested through XRW computations with both theoretical and experimental structure‐factor amplitudes. The tests have shown that the new weighting scheme works optimally if it is applied with theoretically generated X‐ray diffraction data, while it is not advantageous when traditional experimental X‐ray diffraction data (even of very high resolution) are employed. This also led to the conclusion that the use of a specific external parameter λJ for each resolution range might not be a suitable strategy to adopt in XRW calculations exploiting experimental X‐ray data as restraints.